The Effectiveness of Mind Mapping on Students' Memory and Critical Thinking in the Concept of the Life Cycle Concept in Elementary School - Akhmad Jali; Eges Triwahyuni; Eric Dwi Putra (Postgraduate, University of Mataram, 2026)
The ideal goal of IPAS instruction is to create a meaningful learning environment. The IPAS curriculum is designed to foster a deep understanding of the natural phenomena occurring in students’ surroundings. Reality in the field often reveals a gap; for example, at SDN Tanggul Kulon 01, the researcher found evidence of low student memory, characterized by their difficulty in correctly sequencing the stages of a life cycle. The objective of this study is to test the effectiveness of Mind Mapping on students’ memory and critical thinking. This study was designed as an experimental study aimed at investigating the effectiveness of applying the Mind Mapping method on students’ memory and critical thinking. This was evidenced by the results of the t-test, which showed a significant difference in the mean posttest scores between the experimental class and the control class for both dependent variables (p < 0.05). Furthermore, testing the effect size using Cohen’s d coefficient yielded a value of 0.98 for the memory variable and 0.89 for the critical thinking variable, where both results fall within the criteria for a large effect. The integration of spatial visualization, color usage, and keywords in mind maps proved capable of optimizing students’ dual brain functions in encoding and constructing science material in a meaningful way.